Penerapan Model Pembelajaran Think Pair And Share Untuk Meningkatkan Hasil Belajar Siswa Smp Pasraman Jagadnatha Kota Palu - Putu Satya Narayanti (Jurusan Dharma Acarya STAHN-TP Palangka Raya, 2021)
to improve the quality of human resources which will produce output that is faithful to high morality, productive and innovative. A learning cannot be separated from the learning model itself. To improve student learning outcomes, the researchers applied the Think Pair and Share learning model to the Veda material in order to actively involve students in finding creative ideas and being able to solve problems. This study aims to determine the increase in learning outcomes of class VII students of SMP Pasraman Jagadnatha, Palu City. This type of research is a classroom action research conducted in 2 cycles using the Kemmis & Mc. Taggart models. The results showed that there was an increase in student learning outcomes where in cycle I classical learning completeness increased to 62.5% and classical absorption reached 80.37% while cycle II classical learning completeness increased to 93.75% and classical absorption of 85.68 %. The performance indicators in this study have been successful so that it can be concluded that the application of this learning model can improve the learning outcomes of seventh grade students of SMP Pasraman Jagadnatha, Palu City. Kata Kunci : Think Pair and Share, Learning Outcomes, Pasraman Jagadnatha